2021
DOI: 10.24929/lensa.v11i2.166
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Learning Management System Chamilo Materi Gerak Harmonik Sederhana Terhadap Hasil Belajar Peserta Didik

Abstract: Penelitian ini memiliki tujuan agar mendapatkan informasi mengenai efektifitas LMS Chamilo materi gerak harmonik sederhana terhadap hasil belajar peserta didik. Pre-Experimental design terhadap desain penelitian one-group pretest-posttest merupakan metode yang dipakai pada penelitian ini. Peserta didik kelas X SMA Aisyiyah 1 Palembang tahun ajaran 2019/2020 (n=30) menjadi subjek dalam penelitian ini. Sampel diambil berdasarkan teknik purposive sampling. Teknik pengumpulan data dilaksanakan melalui tes tertulis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The development of LMS-based teaching materials will certainly increase motivation and impact student learning outcomes. This statement is undoubtedly by some previous research (Al-Sharhan et al, 2020;Ashrafi et al, 2020;Emelyanova & Voronina, 2014;Fahrudin & Maryam, 2022;Raza et al, 2021;Sumardi et al, 2021;Venter et al, 2012;Wati et al, 2021;Yana & Adam, 2019;Yulfianti & Dewi, 2021). For example, Yulfianti & Dewi (2021) concluded that Learning Management System (LMS) based on google classroom and interest in learning together affect the economic learning outcomes of students of State High School 3 Sidoarjo East Ja a.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The development of LMS-based teaching materials will certainly increase motivation and impact student learning outcomes. This statement is undoubtedly by some previous research (Al-Sharhan et al, 2020;Ashrafi et al, 2020;Emelyanova & Voronina, 2014;Fahrudin & Maryam, 2022;Raza et al, 2021;Sumardi et al, 2021;Venter et al, 2012;Wati et al, 2021;Yana & Adam, 2019;Yulfianti & Dewi, 2021). For example, Yulfianti & Dewi (2021) concluded that Learning Management System (LMS) based on google classroom and interest in learning together affect the economic learning outcomes of students of State High School 3 Sidoarjo East Ja a.…”
Section: Discussionmentioning
confidence: 69%
“…First, the need for education will increase significantly with online learning, as was done during the Covid-19 pandemic. Obtained from online learning will be an attraction for educators and students to choose the learning process where learning becomes available face-to-face (Wati et al, 2021). The Learning Management System-based learning process is becoming one of the leading options in distance education.…”
Section: A Introductionmentioning
confidence: 99%
“…E-learning tools are not only limited to learning materials about circular motion, but can also be developed in other physics learning materials (Wati et al, 2022). Utilization of LMS in effective learning to improve student learning outcomes in physics subjects, namely in the material of Simple Harmonic Motion (Wati et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Online learning content through the LMS application can be made systematic (structured) so that it makes it easier for students to study independently. Various interesting features can facilitate students in mastering various knowledge and skills (Wati, Siahaan and Wiyono, 2021).…”
Section: Introductionmentioning
confidence: 99%